SELECTIVITY OF GILLNETS WITH DIFFERENT CHARACTERISTICS FOR CYPRINUS CARPIO LINNAEUS 1758 CAUGHT IN INLAND WATERS OF TURKEY - Dartay, Murside; Atessahin, Tuncay (Parlar Scientific Publications (P S P), 2017)
In this study, the selectivity of gill nets with different characteristics for Cyprinus carpio (Linnaeus 1758) was investigated between July 2012 and March 2013 in Keban Dam Lake (Elazig, Turkey). For calculating the selectivity parameters and selection curves of the gill nets, the indirect method proposed by Holt (1963) was used. To determine the best fit, different hanging ratios, mesh sizes, and materials were used to produce different gill net characteristics. In this study, the following variations were used: two materials (multimonofilament and multifilament), two hanging ratios (E=0.5 and 0.67), and four mesh sizes (45, 50, 55, and 60 mm). A total of eighteen fishing operations were performed. The initial reproduction length of C. carpio was 38.44 cm in Keban Dam Lake. The initial reproduction length and optimum catching length were compared for best fit to the hanging ratios, mesh sizes, and materials in gill nets. The results showed that the best fit minimum hanging ratio was E=0.67; the best fit mesh size was 60 mm; the best fit material was multi-monofilament gill net; and the optimum catching length was 40.63 vs. 38.64 cm.
Keywords: Cyprinus carpio; gill nets; selectivity; hanging ratio; mesh size; holt method